L’organisation des expressions ritualisées dans le genre épistolaire : étude contrastive sur corpus en français et en chinois - Qianyun Li; Julie Sorba (Discours)
This article is part of a theoretical framework combining text linguistics and contrastive rhetoric. Our objective is to present a contrastive analysis of the conventions codified in letters written in French and in Chinese. The investigation is conducted within an original corpus of argumentative epistolary texts written by a cohort of students in France and in China (2020-2021). Our contrastive analysis aims to identify differences and similarities in the textual organisation of letters in French and Chinese. We propose to study the discursive organisation of opening and closing formulas, highly strategic places for the author’s rhetorical positioning. After a presentation of the structural regularities in the letters in French and Chinese, we will detail the modalities of constitution of our corpus and the collection of data. The contrastive analysis of these formulas allows us to highlight the rhetorical and pragmatic functions chosen first by the writers of the two languages (to expose a thesis, to acknowledge receipt of a letter, to express a personal feeling, to arouse emotion, etc.). As expected, these functions differ on certain points for which we propose explanations in relation to social practices.